A geospatial platform to support visualization, analysis, and prediction of tuberculosis notification in space and time - Thang Phuoc Dao; Xuyen Hong Thi Hoang; Xuyen Hong Thi Hoang; Doanh Ngoc Nguyen; Nghi Quang Huynh; Thang Tat Pham; Dung Thuy Nguyen; Hoa Binh Nguyen; Nam Hoang Do; Hai Viet Nguyen; Cu Huy Dao; Nhung Viet Nguyen; et al. (Frontiers Media S.A., 2022)
BackgroundTuberculosis has caused significant public health and economic burdens in Vietnam over the years. The Vietnam National Tuberculosis Program is facing considerable challenges in its goal to eliminate tuberculosis by 2030, with the COVID-19 pandemic having negatively impacted routine tuberculosis services at all administrative levels. While the turnaround time of tuberculosis infection may delay disease detection, high transportation frequency could potentially mislead epidemiological studies. This study was conducted to develop an online geospatial platform to support healthcare workers in performing data visualization and promoting the active case surveillance in community as well as predicting the TB incidence in space and time.MethodThis geospatial platform was developed using tuberculosis notification data managed by The Vietnam National Tuberculosis Program. The platform allows case distribution to be visualized by administrative level and time. Users can retrieve epidemiological measurements from the platform, which are calculated and visualized both temporally and spatially. The prediction model was developed to predict the TB incidence in space and time.ResultsAn online geospatial platform was developed, which presented the prediction model providing estimates of case detection. There were 400,370 TB cases with bacterial evidence to be included in the study. We estimated that the prevalence of TB in Vietnam was at 414.67 cases per 100.000 population. Ha Noi, Da Nang, and Ho Chi Minh City were predicted as three likely epidemiological hotspots in the near future.ConclusionOur findings indicate that increased efforts should be undertaken to control tuberculosis transmission in these hotspots.